2015
DOI: 10.1007/s00406-014-0572-y
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant NMDA receptor DNA methylation detected by epigenome-wide analysis of hippocampus and prefrontal cortex in major depression

Abstract: Current perspectives on the molecular underpinnings of major depressive disorder (MDD) posit a mechanistic role of epigenetic DNA modifications in mediating the interaction between environmental risk factors and a genetic predisposition. However, conclusive evidence for differential methylation signatures in the brain's epigenome of MDD patients as compared to controls is still lacking. To address this issue, we conducted a pilot study including an epigenome-wide methylation analysis in six individuals diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 46 publications
2
36
0
2
Order By: Relevance
“…The average magnitude of differential methylation between Sham and SNI is approximately 25-30% at all time points. This is a robust shift in methylation state for most DM CpG positions and is on par with that observed in the brain for major depressive disorder [32].…”
Section: Spared Nerve Injury Produces Rapid Large and Persistent Chasupporting
confidence: 56%
“…The average magnitude of differential methylation between Sham and SNI is approximately 25-30% at all time points. This is a robust shift in methylation state for most DM CpG positions and is on par with that observed in the brain for major depressive disorder [32].…”
Section: Spared Nerve Injury Produces Rapid Large and Persistent Chasupporting
confidence: 56%
“…Researchers have taken diverse approaches in examining patterns of DNAm that are associated with major depression; perhaps, not surprisingly, a wide range of findings have been reported. Most studies have found that the the CpG sites (using candidate and epigenome-wide approaches) associated with concurrent depressive symptoms or diagnosis [43][44][45][46][47] were characterized by lower levels of methylation (c.f., ref. 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…We assessed and followed the girls prospectively into adulthood, or until they experienced their first depressive episode. Although some recent research has found no methylation sites that survived correction in relation to MDD 42 , several prior studies reported concurrent depressive symptoms and diagnoses were associated with DNAm using various approaches [43][44][45][46][47] . Given the biological relevance of HPA-axis function to risk for MDD, and that epigenetic variation may reflect combined genetic and environmental risks, we hypothesized that DNAm in CpG sites in HPA-axis genes assessed in early adolescence would predict the onset of MDD.…”
Section: Introductionmentioning
confidence: 97%
“…The hippocampus and prefrontal cortex have been previously linked to emotions and emotional disturbances (Webster et al, 2001;Jin and Maren, 2015). Mechanisms underlying depression based on previous studies include methylation of NMDA receptors in prefrontal cortex and hippocampus (Kaut et al, 2015). In another study, the effectiveness of olanzapine in treatment-resistant depression has been attributed to cellular proliferation in the hippocampus and prefrontal cortex (Kodama et al, 2004).…”
Section: Discussionmentioning
confidence: 99%